Computational Evaluation of Vitamin D3 Binding to KRAS and TGF-β1 in Colorectal Cancer–Associated Signalling Pathways - Shobahah, Jauharotus; Astuti , Wahyuningsih Sri Puji; Herdiansyah, Mochammad Aqilah; Aly, M. Ainun Najib (Jurnal Pijar MIPA, 2026)
Vitamin D3 has been widely investigated for its anticancer properties, yet the structural basis of its interaction with key oncogenic signaling proteins remains incompletely understood. This study aimed to evaluate the molecular interactions between vitamin D3 and KRAS and TGF-β1 using molecular docking and molecular dynamics simulations. Molecular docking analysis was performed using AutoDock Vina, followed by molecular dynamics simulation using CABS-flex to evaluate structural stability using root mean square deviation (RMSD), root mean square fluctuation (RMSF), and radius of gyration (Rg). Comparative benchmarking was performed against the reference inhibitors Sotorasib (KRAS) and Galunisertib (TGF-β pathway). Docking analysis revealed that vitamin D3 binds to KRAS (PDB ID: 4OBE) with a binding affinity of –7.8 kcal/mol, compared to –8.6 kcal/mol for Sotorasib. The interaction was localized within the nucleotide-binding pocket adjacent to the Switch I and Switch II regions, which are critical for conformational regulation. For TGF-β1 (PDB ID: 3KFD), vitamin D3 demonstrated a binding affinity of –8.2 kcal/mol, slightly exceeding that of Galunisertib (–8.1 kcal/mol), with interaction occurring at the receptor-binding interface. Molecular dynamics simulation showed stable complex formation, with RMSD values of 2.79 Å for the KRAS complex and 1.535 Å for the TGF-β1 complex, indicating acceptable structural stability. Residue fluctuation analysis further supported moderate flexibility without global destabilization. These findings suggest that vitamin D3 may function as a multi-target signaling modulator interacting with both intracellular and extracellular regulators of colorectal cancer pathways, providing a structural basis for further experimental investigation.